Crises as Temporality A Critical Reimagination of the Networked Music Ensemble via Live Coding Experimentation - Franco Briones, Alejandro (My University, 2025)
This research seeks to understand the role of music-making in environments heavily mediated by digital networked technology. I argue that music can be understood as a practice capable of anticipating shifts in the current mode of production and regimes of representation. Throughout the project, I unravel a form of subjectivity capable of overcoming the convergence of the crises of care, ecology, representational politics, and economy provoked by a capitalist class that consumes the means for its own reproduction and, with it, the means to reproduce life. This project does so by reimagining the arena of networked music as a collective non-commodified place for care and mutual aid. For this work, I have developed a research creation project that includes artwork, a piece of software for music exploration, and a written thesis, with all three components exploring the themes of temporality and crisis as mediated by networked computation and digital technologies. The first artwork discussed is Temazcal 2: a live-coded documentary co-created with Rolando Hernández. In this work we explore ideas about subjectivity and crises connected to the temazcal: both a sweat-lodge of pre-Hispanic origin common in southern and central Mexico as well as a canonic electroacoustic music work. The second artwork is TimekNot: a Domain Specific (Programming) Language designed to express polytemporal musical ideas and instantiate them as triggered audio samples. The third work is La Fábrica Colapsada: a cybernetic opera exploring the relationship between crisis and time as revealed in the stories of the 2017 earthquake of Mexico City. In observing the earthquake from a disaster studies perspective, I argue that the current music creation context can be seen as a disaster, engulfed in crisis, as well. From this perspective, I argue that within the algorithmic networked ensemble, new ways of framing social relations can allow us to imagine a world where many worlds can fit.
Keywords: networked ensemble; crisis; temporality; algorithmic music; live coding; earthquake; political economy of music; Mexico City